2016
DOI: 10.3109/0284186x.2015.1125015
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of employment and associated factors in long-term lymphoma survivors 10 years after high-dose chemotherapy with autologous stem cell transplantation

Abstract: Background This study examined employment patterns and associated factors in lymphoma survivors treated with high-dose chemotherapy with autologous stem cell transplantation (HDT-ASCT) from diagnosis to a follow-up survey at a mean of 10 years after HDT-ASCT. Patients and methods All lymphoma survivors aged 18 years at HDT-ASCT in Norway from 1987 to 2008, and alive at the end of 2011 were eligible for this cross-sectional study performed in 2012/ 2013. Participants completed a mailed questionnaire. Job status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 18 publications
5
31
1
Order By: Relevance
“…Cost analysis was also in favor of peripheral blood stem cell grafts. Other pretransplantation characteristics, such as socioeconomic status, income, marital status, and psychological distress, are known to impact QoL after AHSCT [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Cost analysis was also in favor of peripheral blood stem cell grafts. Other pretransplantation characteristics, such as socioeconomic status, income, marital status, and psychological distress, are known to impact QoL after AHSCT [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…They found younger age to be associated with an improved RTW rate 28. A recent Norwegian cross-sectional study on 312 long-term lymphoma survivors treated with ASCT between 1987 and 2008 showed that older age was associated with a higher risk of having a not-employed status (odds ratio 1.04 [1.0;1.1]) 18. In the Norwegian study, the not-employed status covered sick leave, disability pension, and old-age pension.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the registries used are designed for administrative purposes, which limited the possibility for us to obtain more detailed information. There is no information on self-reported symptoms like quality of life or physical impairments, which have been shown to be associated with work market affiliation after ASCT 16,18. Future studies might combine register data with questionnaires in order to explore the association between these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data source is a national multicentre cross-sectional follow-up study performed in 2012-2013 consisting of a detailed self-reported questionnaire [2,5], results from a clinical examination [6], as well as data retrieved from patients' charts and the clinical quality register for lymphoma at Oslo University Hospital (OUH). Survivors of HDT-ASCT, treated with BEAM (carmustine, etoposide, cytarabine and melphalan) as high-dose regimen for lymphoma in Norway between 1995 and 2008, aged >= 18 years at HDT-ASCT, alive at survey, residing in Norway and currently not undergoing systemic therapy for active malignancy were eligible (n=355, figure 1).…”
Section: Patientsmentioning
confidence: 99%